Irreversible Investment under Interest Rate Variability: New Results - Luis H. R. Alvarez; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2002)
The current extensive literature on irreversible investment decisions makes the assumption of constant interest rate. In this paper we study the impact of interest rate and revenue variability on the decision to carry out an irreversible investment project. Given the generality of the considered valuation problem, we first provide a thorough mathematical characterization of the problem and develop some new results. Contrary to what previous literature has suggested we establish that interest rate variability may have a profound decelerating or accelerating impact on investment demand depending on whether the current interest rate is below or above the long run steady state interest rate. Moreover, and importantly, allowing for interest rate uncertainty is shown to decelerate rational investment demand by raising both the required exercise premium of the irreversible investment opportunity and the value of waiting. Finally, we demonstrate that increased revenue volatility strengthens the negative impact of interest rate uncertainty and vice versa.
Keywords: 330; irreversible investment; variable interest rates; free boundary problems.